2019
DOI: 10.1186/s13195-019-0541-9
|View full text |Cite|
|
Sign up to set email alerts
|

Amyloid β-protein oligomers promote the uptake of tau fibril seeds potentiating intracellular tau aggregation

Abstract: BackgroundRepeated failure of drug candidates targeting Alzheimer’s disease (AD) in clinical trials likely stems from a lack of understanding of the molecular mechanisms underlying AD pathogenesis. Recent research has highlighted synergistic interactions between aggregated amyloid-β (Aβ) and tau proteins in AD, but the molecular details of how these interactions drive AD pathology remain elusive and speculative.MethodsHere, we test the hypothesis that Aβ potentiates intracellular tau aggregation, and show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 54 publications
(55 reference statements)
5
56
0
2
Order By: Relevance
“…Several research groups studied tau-Aβ cross-seeding [219,220] and found that aggregated Aβ promoted the formation of tau aggregates. It was demonstrated that AβO enhances tau seeding in mouse neurons [221,222] and facilitates intracellular tau aggregation by promoting the uptake of tau seeds. However, transduced Aβ fibrils slightly reduce tau seeding.…”
Section: Aβ-tau Crosstalkmentioning
confidence: 99%
“…Several research groups studied tau-Aβ cross-seeding [219,220] and found that aggregated Aβ promoted the formation of tau aggregates. It was demonstrated that AβO enhances tau seeding in mouse neurons [221,222] and facilitates intracellular tau aggregation by promoting the uptake of tau seeds. However, transduced Aβ fibrils slightly reduce tau seeding.…”
Section: Aβ-tau Crosstalkmentioning
confidence: 99%
“…These results indicate the contribution of mitochondrial ROS to tau oligomer formation and accumulation. Given that Aβ oligomers can seed and promote tau oligomerization and uptake of tau brils [25][26][27] , we propose that Aβ-mediated sustained mitochondrial stress and excessive ROS production could be a potential mechanism underlying Aβ-mediated/enhanced tau oligomers accumulation. Our studies suggest the role of the Aβ/ROS/mitochondria axis in aberrant tau oligomer accumulation, which links to cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, AβO have been shown to enhance, whereas Aβ fibrils reduce, the aggregation of tau (Shin et al 2019b). Furthermore, AβO promote the uptake of tau fibril seeds potentiating intracellular aggregation (Shin et al 2019a) and mediate neurite degeneration (Jin et al 2011). Mechanistic insights into this AβO-tau interaction arise from intriguing new data that demonstrate the involvement of NA, and α2 A adrenergic receptors (α2 A ARs) in mediating tau hyperphosphorylation and Alzheimer’s-related pathology in human and animal samples (Zhang et al 2020).…”
Section: Discussionmentioning
confidence: 99%